2022
DOI: 10.1039/d1nj05245d
|View full text |Cite
|
Sign up to set email alerts
|

Mixed phases of GaOOH/β-Ga2O3 and α-Ga2O3/β-Ga2O3 prepared by high energy ball milling as active photocatalysts for CO2 reduction with water

Abstract: Photocatalytic activity of mixed phases of GaOOH/β-Ga2O3 and α-Ga2O3/β-Ga2O3 for CO2 reduction with water is investigated first time. GaOOH/β-Ga2O3 is synthesized with high energy ball milling of β-Ga2O3 in water,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A study mentioned that the loading of GaOOH on the Ga 2 O 3 photocatalyst can increase the specific surface area for adsorbing more CO 2 for the enhancement of CO evolution. 11 However, in the present case, only 1.0 wt% GaOOH cannot greatly increase the specific surface area of the bare CTO (Table S2†). Hence, it is suggested that the CO 2 adsorption properties of the surface GaOOH layer can enhance the probability of CO 2 reduction by the aid of the Ag cocatalyst.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…A study mentioned that the loading of GaOOH on the Ga 2 O 3 photocatalyst can increase the specific surface area for adsorbing more CO 2 for the enhancement of CO evolution. 11 However, in the present case, only 1.0 wt% GaOOH cannot greatly increase the specific surface area of the bare CTO (Table S2†). Hence, it is suggested that the CO 2 adsorption properties of the surface GaOOH layer can enhance the probability of CO 2 reduction by the aid of the Ag cocatalyst.…”
Section: Resultsmentioning
confidence: 52%
“…8 A Cu/g-C 3 N 4 composite material can increase the yield of CO by adsorbing CO 2 on the g-C 3 N 4 surface and then being utilized by the supported Cu cocatalyst. 9 A composite of GaOOH and Ga 2 O 3 has been reported for the enhancement of the adsorption and the photocatalytic activity for CO 2 reduction, 10,11 where it has been proved that GaOOH has a certain ability to adsorb CO 2 for the improvement of CO evolution. Therefore, the development of a CO 2 adsorbent that is deposited on the photocatalyst surface might be a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…As for the reaction mechanism, we have proposed the following redox like chemical reaction. 19 Initially the surface of α-Ga 2 O 3 is hydroxidized with water to be GaOOH. Then UV light illumination dissociated the GaOOH as 2GaOOH → α-Ga 2 O 3 + H 2 + 1/2O 2 …”
Section: Resultsmentioning
confidence: 99%